How does Information Exposure Affect Public Attitudes Toward GMO in China? The mediating and moderating roles of Conspiracy Belief and Knowledge - Du, Zhitao; Xiao, Yuqi; Xu, Jinghong (Frontiers in Psychology, 2022)
Background: In China, controversy about genetically modified organisms (GMOs) is ongoing, and the public regard GMO as a "product of a conspiracy", which affects people’s attitudes (PAs) toward GMOs. Beliefs in conspiracy theories (BCT) are formed from the information that people are exposed to. Information exposure not only constructs a pseudo-environment for individuals to perceive the world, but also generates external stimuli for their mental states and attitudes. People’s knowledge and self-assessed knowledge play an important moderating role in this process. Method: This study adopted the stimulus-organism-response (SOR) model to test the effect of the independent variable of information exposure on the dependent variable of PAs toward GMOs using BCT as mediator variables. Objective knowledge and self-assessed knowledge were introduced as moderator variables to explore the different influences of knowledge differences. A survey of Chinese adults was conducted in February 2022, and partial least squares structural equation modeling (PLS-SEM) was employed to estimate the multi-construct relationships. Results: Information exposure had a significant direct effect on PAs toward GMOs. BCT also played a significant mediating role. Unofficial information exposure reinforced beliefs in conspiracy theories. Stronger beliefs in conspiracy theories reduced people’s willingness to consume GMO foods and made them pessimistic about the development prospects of GMO foods. In contrast, exposure to official information weakened people’s beliefs in conspiracy theories and increased their willingness to consume GMO foods, leading to optimism about their prospects. In addition, the level of knowledge had a moderating role. Individual’s objective knowledge can effectively reduce the negative impact of conspiracy beliefs on attitudes toward GM development. Conversely, individual’s self-assessment knowledge can enhance the negative impact of conspiracy beliefs on attitudes toward GM development. Conclusion: Based on psychological and cognitive dimensions, this study provides a new perspective on how information exposure affects attitudes toward GMO and enriches the variable measurement dimension of knowledge. Simultaneously, it provides a localized explanation of the factors affecting attitudes toward GMOs in China, providing a new theoretical basis for the subsequent development strategy of GMO foods.